Avoiding Zoom Fatigue: The Uses and Gratifications on Social Media - Festy Rahma Hidayati; Irwansyah Irwansyah (CHANNEL: Jurnal Komunikasi, 2021)
The Corona Virus Disease 2019 (Covid-19) pandemic has forced the government to implement Large-Scale Social Restrictions (PSBB) several times. As a result of this policy, it is mandatory to implement the Working From Home (WFH) policy. The company then facilitates its employee with virtual meeting applications, such as Zoom. On the other hand, WFH has a frequent impact and the length of time spent in virtual meetings causes zoom fatigue. The purpose of this study is to determine the uses and gratification of social media users to avoid zoom fatigue when working from home during the Covid-19 pandemic. Social media users use it as a means of fulfilling usability and satisfaction based on the media chosen. This study will describe the uses and gratification of using social media during WFH to avoid â€œZoom fatigueâ€ based on Computer-Mediated Communication Theory and Uses and Gratification Theory.The study uses a qualitative approach with an explorative method to find or formulate problems from a phenomenon.Â  The study uses literature studies based on scientific articles in international and national journals related to the use of social media based on the Uses and Gratification theory in the last ten years. For further exploration, the researcher conducted in-depth semi-structured interviews via email and telephone with three informants. The interview results revealed the uses and gratification for social media users to avoid zoom fatigue while undergoing WFH during the pandemic Covid-19. Social media as a source of entertainment and relaxation, a source of information, spending time, interacting and expressing opinions, and monitoring. The researcher hopes that the results of this study can fill the lack of existing research related to the uses and gratification of social media based on Computer-Mediated Communication and Uses and Gratification Theory. It can also contribute knowledge to practitioners who are content creators, marketing agencies, and online shop owners to optimize content to get high user engagement.